The influence of the "fragmented city" on wellbeing: Do mixed neighbourhoods affect young adults' life trajectories in Bogota? - Juan Fernando Bucheli (Journal of Urban Management, 2022)
This article investigates the effects that living in heterogeneous neighbourhoods may have on well-being, in order to shed light on the potential consequences of promoting residential mix policies. Using propensity score matching models, the study investigates whether 120 disadvantaged young adults located in a heterogeneous neighbourhood in Bogota scored differently on a battery of indicators of well-being compared to disadvantaged young adults located in a homogenous neighbourhood. Results suggest that when young adults live close to better-off peers, those in heterogeneous neighbourhoods are more likely to experience reduced capability scores than those in homogeneous neighbourhoods.
Keywords: 710; Bogota; Capability approach; Propensity score matching; Urban segregation; Young adults